Growth retardation in Turner syndrome: aneuploidy, rather than specific gene loss, may explain growth failure - Haverkamp, Fritz; Wölfle, J.; Zerres, K.; Butenandt, O.; Amendt, P.; Hauffa, B. P.; Weimann, E.; Bettendorf, Markus; Keller, E.; Mühlenberg, R.; Partsch, C. J.; Sippell, W. G.; et al. (The journal of clinical endocrinology & metabolism, 1999)
The etiology of short stature (SST) in Turner syndrome (TS) is still a subject of speculation. A variety of hypotheses have been put forward, from SST as a result of increased intrauterine tissue pressure after fetal lymphedema to haploinsufficiency of a specific growth gene(s). These hypotheses have various statistical-auxological implications on the growth distribution in TS. Empirical research has provided no clear evidence for any of these theories, but the well known correlation between patients’ and midparental height (MPH) could be established. The influence of undetected mosaic status has often been cited as a major problem in the investigation of growth in TS. However, an assessment of mosaic status (simultaneous analysis of karyotype and phenotype) and its effect on growth with inclusion of MPH has been not yet carried out for a large sample. The aim of this study was to evaluate growth and its complex relationship to mosaic status and MPH in TS.In a mixed cross-sectional and longitudinal study we retrospectively analyzed the auxological and clinical data of 447 patients with a pure loss of X-chromosomal material (n = 381 with 45,X0; n = 66 mosaics). The 447 patients were selected from a series of 609 consecutive patients with TS. To assess the effect of mosaic status on growth, we computed a bifactorial analysis of variance (phenotype, karyotype), including MPH as a covariate.In line with the mosaic hypothesis, we found a correlation between individual loss of X-chromosomal material and phenotypical expressivity. In contrast, no correlation was found with respect to growth. With respect to MPH, we found growth retardation (GR) even in those patients with “normal” height above the third percentile (−2 or more sd score).The interindividual variance of GR in TS (comparable to growth variance in the normal population) seems to be unrelated to other TS-specific factors (e.g. mosaic status or single gene loss). Instead, both interindividual variance and the global growth shift distribution are best explained by the presence of an unspecific aneuploidic effect. Furthermore, consideration of patient height in relation to MPH should lead to a better understanding of the nature of GR in TS than the commonly used, strictly qualitative definition of SST.